Rapid detection of sucrose adulteration in honey using Fourier transform infrared spectroscopy - Cengiz, Mehmet Fatih; Durak, M. Zeki (TAYLOR & FRANCIS INC, 2019)
Honey authenticity is of great importance for commercial and health reasons. The most common adulteration methods are overfeeding of bees with sugar or by adding sucrose. In the study, a Fourier transform infrared spectroscopy based on chemometric method, a partial least squares, for determination of sucrose sirup adulteration of Turkish honeys was improved. For this purpose, honey samples were adulterated with known amounts of sucrose sirup in concentrations ranging between 5.94 and 27.80%. A calibration curve was constructed within 992-923 cm(-1) with the regression coefficient of 0.999. Obtained results from the spectra were confirmed by high performance liquid chromatography-refractive index detector and a good correlation was found between the results of the spectroscopic and chromatographic methods. Additionally, some method validation parameters (linearity, repeatability, limit of detection, and quantification) of the spectroscopic method were studied and obtained results were compared with chromatographic method. To prove the usefulness of the method, twenty different honey samples were collected from markets in Turkey and analyzed for sucrose contents. The results indicated that predicted sucrose concentration of honey samples by the spectroscopic method ranged between 4.52 and 15.16% and results were confirmed by the chromatographic method with high correlation (correlation coefficient = 92%). The results of the present indicated showed that adulteration ratio of honey samples by sugar addition can be detected using Fourier transform infrared spectroscopy technique in a short time with high accuracy. In conclusion, this method could be regarded as a new alternative technique for routine analysis in quality control of honey samples.
Keywords: Adulteration; FTIR; honey; HPLC; sucrose; CANE SUGAR ADULTERATION; FRUCTOSE CORN SYRUP; FTIR SPECTROSCOPY; QUANTIFICATION; CLASSIFICATION; PURE; Spectroscopy